THE INFLUENCE OF PRODUCT QUALITY AND LOCATION ON CONSUMER PURCHASE DECISIONS: A CASE STUDY OF KOPI KILA - Putri, Alya Ayunda; Sukatmajaya, Ahmad (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to find out